Feasible and Rapid Screening of IDH1/2 and FLT3-TKD2 Mutations by High-Resolution Melting for Patients with Acute Myeloid Leukemia - José Vicente Gil; Sandra de las Heras; Alberto Miralles; Claudia Sargas; Marta Llop; Rebeca Rodríguez-Veiga; Laura Torres-Miñana; Blanca Boluda; Isabel Cano-Ferri; Evelyn Acuña-Cruz; Irene Navarro; Pilar Lloret-Madrid; et al. (Diagnostics)
Background: In recent years, numerous recurrently mutated genes have been identified in acute myeloid leukemia (AML), some of which, such as FLT3 and IDH1/2, serve as therapeutic targets, offering new treatment options. Rapid mutational analysis is crucial for timely and optimal therapy selection. This study aims to develop and validate a rapid, cost-effective, and sensitive screening method for detecting IDH1, IDH2, and FLT3-TKD2 mutations using polymerase chain reaction (PCR) and high-resolution melting curve analysis (HRM). Methods: A PCR-HRM assay was developed to simultaneously detect mutations in IDH1, IDH2, and FLT3-TKD2. The method was applied to a cohort of 1363 AML patients, and its performance, including turnaround time, was evaluated through comparison with next-generation sequencing (NGS) results. Results: The PCR-HRM method demonstrated a positive percent agreement of 98%, 98%, and 92% for IDH1, IDH2, and FLT3-TKD2, respectively, and a negative percent agreement of 100% for all three genes compared to NGS. No false positives were observed, and false negatives were detected in less than 1% of cases, mostly in FLT3-TKD2, all occurring below the established limit of detection. The turnaround time and cost of PCR-HRM were significantly lower than those of NGS. Conclusions: This method offers a highly sensitive, specific, and time-efficient approach for the simultaneous detection of IDH1, IDH2, and FLT3-TKD2 mutations in AML patients. Its rapid turnaround time and cost-effectiveness make it a valuable tool for routine clinical screening, facilitating timely and targeted treatment decisions.